Microbial Biodegradation of Plastics: A Sustainable Approach to Pollution Control - Dr. Rajagopal B,; Dr. Thangavelu A. U,; A S Jagadheeswari, (The Bioscan, 2025)
Plastic pollutants caused by synthetic materials do not naturally break and are difficult to take out which is why it has become a global problem. Landfills and incinerators damage the environment, so seeking sustainable solutions matters a lot today. Natural processes with microbes can break plastics apart so they are safe for the environment. It goes into detail about studies that investigate plastic breakdown by microbes, listing the species involved and the methos they employ and also explaining any variables that affect their work. A number of studies indicate that progress in genetics and microbial fields has led to faster decomposition of toxins. The material covers the obstacles including the slow breakup of plastic, possible harm from environmental changes and the difficulty in spreading the practice. With the use of studies and different experiments, the research looks for methods to apply microbial biodegradation for handling pollution. Researchers in biodegradation investigate the ways that microbial enzymes as hydrolases and oxygenases assist biodegradation as well as what environmental factors benefit it the most. At the closing, we review possible solutions for plastic pollution that involve synthetic biology, biotechnology and government laws. It shows that having microbes biodegrade plastic as this is a major pathway for addressing plastic waste and encourages people to find solutions with scientific exploration and engineering methods.